Immunohistochemistry as a detection tool for ion channels involved in dental pain signaling - Rosmaliza Ramli; Siti Norasikin Mohd Nafi; Nor Azura Ahmad Tarmidzi; Nurulezah Hasbullah; Nurhafizah Ghani (Saudi Dental Journal, 2022)
Background: Despite advances in pain detection, diagnosis, and management, the prevalence of dental pain is still on the rise. Although dental pain is not directly related to fatal outcomes, the two most common types of dental pain—dental caries and dentin hypersensitivity—have a significant impact on an individual’s quality of life. Understanding the mechanism of the pain pathway is one of the crucial steps in providing better treatment for these patients. Ion channels are critical biomolecules that have been the subject of dental study owing to their roles in the transmission and transduction of external stimuli, as well as in the control and perception of pain. Numerous immunohistochemical (IHC) staining approaches have also been used to identify the many ion channels implicated in peripheral pain signaling in dental pulp. Highlight: This review highlights the critical steps in IHC and its role in the detection of ion channels involved in the dental pain signaling pathway. Conclusion: The key ion channels identified using IHC and whose functions have been widely researched in dental tissues are addressed in this review article.